2020
DOI: 10.1002/ase.1933
|View full text |Cite
|
Sign up to set email alerts
|

Phenoxyethanol‐Based Embalming for Anatomy Teaching: An 18 Years' Experience with Crosado Embalming at the University of Otago in New Zealand

Abstract: Embalming fixatives such as formaldehyde and phenol have been associated with occupational health hazards. While anatomists aim at replacing these chemicals, this seems presently unfeasible in particular for formaldehyde. Furthermore, fixation protocols usually require well-equipped facilities with highly experienced staff to achieve good fixation results in spite of only a minimal use of formaldehyde. Combining these aspects, a technique robust enough to be carried out by morticians is presented, resulting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 67 publications
(102 reference statements)
1
61
0
Order By: Relevance
“…The here reported B strength of 67 MPa is similar to the values of 85 MPa obtained from frontal and parietal regions of eight fresh-frozen cadavers using a testing velocity of 30,000 mm/min 12 and the 64 to 86 MPa obtained from 114 unembalmed fronto-parietal samples using a testing speed of 0.06 mm/min 10 . A study involving Crosado-embalmed 42 cadavers using an identical testing velocity as in the given study of 10 mm/min reported a lower B strength of 42 MPa and 53 MPa for the two investigated human neurocrania 6 , likely due to an embrittlement of the tissue following the chemical treatment or a statistical bias caused by the low sample size in the former work. The B strength of the composite group in this given study decreased with age, presumably caused by the concomitant age-related thickening of the samples without a concurrent increase of F max values.…”
Section: Discussionmentioning
confidence: 64%
“…The here reported B strength of 67 MPa is similar to the values of 85 MPa obtained from frontal and parietal regions of eight fresh-frozen cadavers using a testing velocity of 30,000 mm/min 12 and the 64 to 86 MPa obtained from 114 unembalmed fronto-parietal samples using a testing speed of 0.06 mm/min 10 . A study involving Crosado-embalmed 42 cadavers using an identical testing velocity as in the given study of 10 mm/min reported a lower B strength of 42 MPa and 53 MPa for the two investigated human neurocrania 6 , likely due to an embrittlement of the tissue following the chemical treatment or a statistical bias caused by the low sample size in the former work. The B strength of the composite group in this given study decreased with age, presumably caused by the concomitant age-related thickening of the samples without a concurrent increase of F max values.…”
Section: Discussionmentioning
confidence: 64%
“…Certain embalming methods reduce the risk of articular branches being damaged as they make structures more easily identifiable and forms the surrounding tissue in a suitable consistency for blunt dissection. Ethanol-based 102 , phenoxyethanol or Thiel 103 embalmed cadavers may be more suitable for performing future macroscopic studies of nerves, ligaments and muscles in terms of haptics, compared to the stiffer tissues resulting from formaldehyde and ethanol embalming 104 . These specific embalming methods have not been employed to date when assessing HC innervation, this is likely because of the known regional differences in anatomical departments which favor one special embalming technique.…”
Section: Discussionmentioning
confidence: 99%
“…These specific embalming methods have not been employed to date when assessing HC innervation, this is likely because of the known regional differences in anatomical departments which favor one special embalming technique. Authors should consider the fixation of cadavers used in future work thoroughly as Thiel embalming does not permit for histologic assessment of small nerves 104 .…”
Section: Discussionmentioning
confidence: 99%
“…A total of nine complexes comprising of the human AT, adjacent calcaneus and PF (subsequently referred to as AT-calcaneus-PF complex) were retrieved post mortem (mean age 74, age range 28 to 93). One of the complexes was used for histological assessment (28-year-old male), two for plastination (87-year-old female, corresponding to one left and one right complex) and six for mechanical testing (four phenoxyethanol-based embalmed cadavers 12 , left and right complex was used of two cadavers, two right complexes of two other cadavers, mean age 82 years, 3 males, 1 female). The histologically processed AT-calcaneus-PF complex was retrieved at the Institute of Legal Medicine, University of Leipzig, Germany during leg preparation and the remaining ones were acquired from bequeathed cadavers for medical education and research purposes at the Department of Anatomy of the University of Otago in Dunedin, New Zealand.…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, the minute samples size was limited by the number of available tissues. The mechanically tested samples in this study were embalmed using a phenoxyethanol-based fixative 12 and subsequently decalcified by means of a 10wt% EDTA solution, which might have influenced the biomechanical properties. However, the biomechanical purpose of the given study was to compare the biomechanical properties of several sub-structures of the AT-calcaneus-PF complex to each other with special interest of the change of the individual parameters from proximal to distal rather than giving a detailed lifelike material description of the aforementioned.…”
Section: Limitationsmentioning
confidence: 99%